Penguatan Literasi Melalui Pendirian Perpustakaan Digital - Nasrul Amin , Moh.; Husna, Asmaul (Ngaliman: Jurnal Pengabdian Kepada Masyarakat, 2022)
Weak literacy in school-age children is a common discussion in Indonesian society, with various factors causing this, including due to culture and the availability of supporting facilities and infrastructure. Therefore, in this service-based research, researchers try to analyze the increase in literacy of school-age children by assisting in the establishment of digital libraries. Libraries which are considered as a source of knowledge have an important role in providing knowledge to library users in utilizing digital information both in learning and having an impact on life, including in increasing literacy in society in general. Digital library is the application of information technology that is used as a means to obtain, store, and disseminate information packaged in digital form. In simple terms, it can be said as a storage place for library collections in digital form. Digital libraries make it easy for users to access electronic information sources with tools that are easily accessible at limited times and opportunities. Users are no longer physically bound to library service hours where users have to visit the library directly to obtain information. Therefore, digital libraries can be used as a means and solution to the problem of limited access.